Biomechanical properties of a buzz-pollinated flower - Brito, Vinicius Lourenço Garcia (R Soc Open Sci, 2020)
Approximately half of all bee species use vibrations to remove pollen from plants with diverse floral morphologies. In many buzz-pollinated flowers, these mechanical vibrations generated by bees are transmitted through floral tissues, principally pollen-containing anthers, causing pollen to be ejected from small openings (pores or slits) at the tip of the stamen. Despite the importance of substrate-borne vibrations for both bees and plants, few studies to date have characterized the transmission properties of floral vibrations. In this study, we use contactless laser vibrometry to evaluate the transmission of vibrations in the corolla and anthers of buzz-pollinated flowers of Solanum rostratum, and measure vibrations in three spatial axes. We found that floral vibrations conserve their dominant frequency (300 Hz) as they are transmitted throughout the flower. We also found that vibration amplitude at anthers and petals can be up to greater than 400% higher than input amplitude applied at the receptacle at the base of the flower, and that anthers vibrate with a higher amplitude velocity than petals. Together, these results suggest that vibrations travel differently through floral structures and across different spatial axes. As pollen release is a function of vibration amplitude, we conjecture that bees might benefit from applying vibrations in the axes associated with higher vibration amplification.